1981
DOI: 10.1111/j.1600-0765.1981.tb02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular junctions and the permeability barrier in the junctional epithelium

Abstract: The morphology and distribution of intercellular junctions were studied in the clinically normal junctional epithelium of dogs by freeze‐fracture and thin sectioning. Desmosomes were found in cells of the coronal and apical regions of the junctional epithelium. The occurrence values for desmosomes were low in comparison with those of other oral epithelia. Gap junctions were also observed in cells of the junctional epithelium, often in association with desmosomes. These were usually small, their diameter varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Furthermore, a significant proportion of this area in an individual with periodontitis is composed of ulcerated epithelium and the integrity of the epithelium is decreased through alteration of intercellular substance by various enzymes. Penetration of the epithelial barrier is probably associated with the vast extent of intercellular spaces and the lack of desmosomes, especially in the junctional epithelium (Saito et al 1981). This lack of epithelial barrier function aids the ingress of bacteria into the underlying tissues.…”
Section: Effect Of Periodontal Inflammation On Oral Bacteraemiamentioning
confidence: 99%
“…Furthermore, a significant proportion of this area in an individual with periodontitis is composed of ulcerated epithelium and the integrity of the epithelium is decreased through alteration of intercellular substance by various enzymes. Penetration of the epithelial barrier is probably associated with the vast extent of intercellular spaces and the lack of desmosomes, especially in the junctional epithelium (Saito et al 1981). This lack of epithelial barrier function aids the ingress of bacteria into the underlying tissues.…”
Section: Effect Of Periodontal Inflammation On Oral Bacteraemiamentioning
confidence: 99%
“…Interestingly, although the claudin family consists of at least 24 members (4), no significant changes in the expression of other claudin genes were identified in diseased tissues. Although tight junctions in gingival junctional epithelium are much less developed (17), we have recently reported that claudin‐1 exists in rat gingiva junctional epithelium (9). In this study a reduction in expression of the claudin‐1 gene was validated with expression of the claudin‐1 protein, which was also significantly lower in the same experimental animals.…”
Section: Discussionmentioning
confidence: 99%
“…He suggests that this may be a pointless pursuit, mainly since even non-keratinized epithelia may offer resistance to the penetration of many substances (35,38) and 41 (1983) since keratinization of the highly permeable (28,30) junctional epithelium may lead to loss of epithelial attachment to the tooth surface and thus be harmful. Although this latter point may be well taken, it should be kept in mind that in spite of the intensive antibacterial therapy over considerable periods of time in this and other (2, 5 , 32) studies, keratinization of the junctional epithelium in situ has never been reported as a result of antibacterial therapy and may not be readily achieved (30,41).…”
Section: Discussionmentioning
confidence: 99%